Reducing the Cultivation of Opium Poppies in Southern Afghanistan - Greenfield, Victoria A. (RAND Corporation, 2015)
This report identifies drivers of opium poppy cultivation in southern Afghanistan and assesses the positive and negative effects of programs designed to promote rural development, eradicate opium poppies, or otherwise create incentives for farmers cultivate less opium poppy. The authors also provide advice on how to design programs that might better serve to reduce the cultivation of opium poppies in southern Afghanistan over the long term.